Religion and Spirituality in the Face of Illness: How Cancer, Cardiac, and HIV Patients Describe their Spirituality/Religiosity - Woods, Teresa E.; Ironson, Gail H. (Journal of health psychology, 1999)
This study reports the results of semi-structured interviews conducted with 60 medically ill (cancer, myocardial infarction, HIV/AIDS) people in an attempt to define what people facing a life-threatening illness mean when they say they are ‘spiritual’ or ‘religious’. Questions were asked about beliefs and affective, behavioral, and somatic realms. Subjects initially self-identified as considering themselves to be spiritual, religious, or both. While some similarities existed between the groups (e.g. amount of time spent in prayer, beliefs set the tone for their life, give them a sense of well-being, guidance, a sense of right and wrong, a connection to God, and a sense they will live on in some form), significant differences were discovered in overall belief systems, as well as in interpretation of the mechanisms whereby subjects' beliefs impacted their health and their recovery. Those identifying as spiritual described recovery and healing as happening through them whereas those identifying as religious were more likely to say it happens to them. In addition, significant differences existed between the groups in their overall view of God, self, world, and others. Implications for future studies are discussed.